Basic structural motif and major biophysical properties of Amyloid-beta are encoded in the fragment 18-35 - Chandrakesan, Muralidharan; Sarkar, Bidyut; Mithu, Venus Singh; Rajiv M. Abhyankar; Bhowmik, Debanjan; Nag, Suman; Sahoo, Bankanidhi; Shah, Riddhi; Gurav, Sushma; Banerjee, Raja; Dandekar, Sucheta; Jose, Jaya C.; et al. (Chemical Physics, 2013)
Aggregation and misfolding of the amyloid beta (A beta) peptide is thought to initiate Alzheimer's disease (AD). Here we study the role played by its central segment (A beta(18-35)) in determining these properties. A beta(18-35) has a solubility of 18 mu M. The soluble fraction consists mainly of small oligomers, which have mixed beta-sheet and random coil structures. The monomer is mostly a random coil with some residual compactness. Aggregated A beta(18-35) forms fibrils of width 3.0 +/- 0.7 nm, which is consistent with a hairpin shape. Each of these properties has a close similarity to A beta(40). Remarkably, solid state NMR indicates that the fibrils also retain the secondary structure and tertiary contacts of A beta(40). This is the shortest fragment of A beta reported so far which preserves its fibrillar architecture, including the hairpin turn, as well as its solution phase conformational properties. Residues 18-35 should therefore be a key target of AD therapeutics. (C) 2013 Published by Elsevier B. V.
Keywords: Alzheimer's disease; Fluorescence correlation spectroscopy; Protein aggregation; Solid-state NMR

Beta self-association and adsorption on a hydrophobic nanosurface: competitive effects and the detection of small oligomers via electrical response - Jana, Asis K.; Sengupta, Neelanjana (Soft Matter, 2015)
Treatment of Alzheimer's disease (AD) is impeded by the lack of effective early diagnostic methods. Small, soluble A beta globulomers play a major role in AD neurotoxicity, and detecting their presence in aqueous fluids could lead to suitable sensors. We evaluate the adsorption behavior of small A beta oligomers on the surface of a single walled carbon nanotube of high curvature. While the intrinsic self-assembly propensity of A beta is markedly hindered by adsorption, the oligomeric units show high degrees of surface immobilization. Immobilized complexes are capable of oligomeric growth, but with a shifted monomer-oligomer equilibrium compared to the free states. In the presence of an ionic solution and suitable external electric fields, magnitudes of the current blockades are found to be sensitive to the oligomeric number of the adsorbed complex. However, this sensitivity gradually diminishes with increasing oligomeric size. The results provide a proof-of-concept basis for further investigations in the design of sensors for detecting the toxic small oligomers of A beta.